Role Model Media Miniatur untuk Meningkatkan Kesiapsiagaan Mahasiswa dalam Fase Mitigasi Manajemen Bencana di Universitas Kusuma Husada Surakarta - Singgih Nugroho; Gatot Suparmanto; Sutiyo Dani Saputro (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Disaster is an event that threatens and disrupts people's lives caused by natural factors, non-natural factors, as well as human factors, resulting in human casualties, environmental damage, loss of property, and psychological impacts. The purpose of this study was to analyze the effect of the Miniature Media Role Model on student preparedness in the disaster management mitigation phase at Kusuma Husada University, Surakarta. This type of research was an experimental study with a one group pre-test and post-test design. Respondents in the study were 36 KNC students, who were selected by purposive sampling technique. The way of collecting data was filling out a questionnaire about disaster mitigation preparedness. Data were analyzed using the Wilcoxon test. The results of data analysis showed a p-value of 0.000. Furthermore, it was concluded that there was an influence of the Media Miniature Role Model on student preparedness in the disaster management mitigation phase at Kusuma Husada University, Surakarta.Keywords: mitigation; miniature media role models; disaster preparedness ABSTRAK Bencana merupakan peristiwa yang mengancam dan menganggu kehidupan masyarakat yang disebabkan oleh faktor alam, faktor non alam, maupun faktor manusia, sehingga mengakibatkan timbulnya korban jiwa manusia, kerusakan lingkungan, kerugian harta benda, dan dampak psikologis. Tujuan penelitian ini adalah menganalisis pengaruh Role Model Media Miniatur terhadap kesiapsiagaan mahasiswa dalam fase mitigasi manajemen bencana di Universitas Kusuma Husada Surakarta. Jenis penelitian ini adalah studi eksperimental dengan rancangan one group pre-test and post-test. Responden pada penelitian adalah 36 mahasiswa KNC, yang dipilih dengan teknik purposive sampling. Cara pengumpulan data adalah pengisian kuesioner tentang kesiapsiagaan mitigasi bencana. Data dianalisis menggunakan uji Wilcoxon. Hasil analisis data menunjukkan nilai p = 0,000. Selanjutnya disimpulkan bahwa ada pengeruh Role Model Media Miniatur terhadap kesiapsiagaan mahasiswa dalam fase mitigasi manajemen bencana di Universitas Kusuma Husada Surakarta.Kata kunci: mitigasi; role model media miniatur; kesiapsiagaan bencana